ADENOMYOSIS AMONG SAMPLES FROM HYSTERECTOMY DUE TO ABNORMAL UTERINE BLEEDING - Pervez, Shagufta Nasir; Javed, Khalid (Journal of Ayub Medical College Abbottabad, 2013)
Background: Adenomyosis is one of the most common, yet under diagnosed, underlying cause of abnormal uterine bleeding. We aimed to evaluate the presence of adenomyosis among the patients who presented with abnormal uterine bleeding. Methods: This was a retrospective study carried out on hysterectomy specimens of subjects who presented to the gynaecologist with the complaint of abnormal uterine bleeding not responding to conservative treatment. Excluded are the hysterectomies performed for malignant pelvic neoplasms and hysterectomy following labour for postpartum haemorrhage. Results: A total of 861 women underwent hysterectomy out of which 779 were abdominal and 82 vaginal from Jan 2008 to Dec 2012. Adenomyosis was found in 296 of the 861 specimens studied. The most frequent combination of diagnosis was leiomyoma and adenomyosis. Pathologic conditions associated with adenomyosis were: leiomyomas 150 (50.6%), endometrial polyp 16 (5.4%), genital prolapse 12 (4.05%), chronic endometritis 10 (3.3%), endometrial hyperplasia 5 (1.6%), endocervical polyps 2 (0.6%). Conclusion: Adenomyosis is a common pathologic finding significantly related to reproductive and menstrual characteristics of the patients. Keywords: Adenomyosis, Hysterectomy, Leiomyoma